Old Testament theology : flowering and future - Ollenburger, Ben C.; Ollenburger, Ben C. (Winona Lake, Indiana, Eisenbrauns, 2004)
In this extensively revised and updated edition of The Flowering of Old Testament Theology, Professor Ollenburger provides help for beginning theological students, who are frequently overwhelmed by the proliferation of volumes dealing with Old Testament theology, to say nothing of the variety of approaches used in these works. This textbook has been re-issued with a new title, Old Testament Theology: Flowering and Future. Selected essays include key theological statements of Otto Eissfeldt, Walther Eichrodt, Theodorus C. Vriezen, George E. Wright, Gerhard von Rad, Walther Zimmerli, John L. McKenzie, Ronald E. Clements, Walter C. Kaiser Jr., Samuel L. Terrien, Claus Westermann, Brevard S. Childs, Rolf Knierim, Horst D. Preuss, Walter Brueggemann, Paul R. House, Bernhard W. Anderson, Erhard S. Gerstenberger, Hartmut Gese, Phyllis Trible, Jon D. Levenson, John H. Sailhamer, Gunther H. Wittenberg, James Barr, R.W.L. Moberly, and Mark G. Brett. An appendix contains Johann P. Gabler's 1787 seminal essay on biblical theology. An extensive bibliography and indexes of authorities and Scripture references conclude the volume. - Publisher.
Old Testament theology before 1933 / Ben C. Ollenburger -- The history of Israelite-Jewish religion and Old Testament theology / Otto Eissfeldt -- Does Old Testament theology still have independent significance within Old Testament scholarship? ; Covenant / Walther Eichrodt -- The nature of the knowledge of God / Theodorus C. Vriezen -- God the warrior / George Ernest Wright -- Eighth-century prophecy / Gerhard von Rad -- Life before God / Walther Zimmerli -- Cult / John L. McKenzie -- Law and promise / Ronald E. Clements -- Promise / Walter C. Kaiser Jr. -- Presence in absence / Samuel Lucien Terrien -- God's judgment and God's mercy / Claus Westermann -- Land and lifestyle / Elmer A. Martens -- Canon / Brevard S. Childs -- Cosmos and history / Rold Knierim -- Exodus and election / Horst Dietrich Preuss -- Israel's testimony / Walter Brueggemann -- Ruth in the canon / Paul R. House -- Royal covenant / Bernhard W. Anderson -- One God, changing theologies / Erhard S. Gerstenberger -- Tradition history / Hartmut Gese -- Overture for a feminist biblical theology / Phyllis Trible -- Creation and covenant / Jon D. Levenson -- Canon and composition / John H. Sailhamer -- Contextual theology and resistance / Gunther Hermann Wittenberg -- "Real" theology and biblical theology / James Barr -- The Bible, theology, and faith / R.W.L. Moberly -- The future of Old Testament theology / Mark G. Brett -- An oration on the proper distinction between biblical and dogmatic theology and the specific objectives of each / Johann P. Gabler.
Revision of: The flowering of Old Testament theology. 1992.
Includes bibliographical references (pages 507-526) and indexes.
Keywords: Bible. -- Theology; Bible. -- Criticism, interpretation, etc. -- History -- 20th century